2019
DOI: 10.3390/nano9070983
|View full text |Cite
|
Sign up to set email alerts
|

Improved Surface-Enhanced Raman Scattering Properties of ZrO2 Nanoparticles by Zn Doping

Abstract: In this study, ZrO2 and Zn–ZrO2 nanoparticles (NPs) with a series of Zn ion doping amounts were synthesized by the sol-gel process and utilized as substrates for surface-enhanced Raman scattering (SERS). After absorbing the probing molecule 4–mercaptobenzoic acid, the SERS signal intensities of Zn–ZrO2 NPs were all greater than that of the pure ZrO2. The 1% Zn doping concentration ZrO2 NPs exhibited the highest SERS enhancement, with an enhancement factor (EF) value of up to 104. X-ray diffraction, X-ray photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 41 publications
2
15
0
1
Order By: Relevance
“…To further prove the difference of assembly modes from the perspective of the overall structure, ultraviolet–visible (UV–vis) absorbance spectra of Ink-01, Ink-02, and Ink-03 at different temperatures were tested, as shown in Figure . The absorbance peak located at 300–400 nm was considered to be generated from the valence band–conduction band electron transition of emerging zirconia composited with polymers. As the testing temperature increased, the PAM/ZrO x composite cluster gradually formed and the sol–gel transition of the ink sample occurred, which can lead to the shift and intensity change of the absorption peak. For Ink-01, the spectrum changed little below 45 °C, and the absorbance peak intensity significantly increased when the temperature reached 80 °C.…”
Section: Resultsmentioning
confidence: 99%
“…To further prove the difference of assembly modes from the perspective of the overall structure, ultraviolet–visible (UV–vis) absorbance spectra of Ink-01, Ink-02, and Ink-03 at different temperatures were tested, as shown in Figure . The absorbance peak located at 300–400 nm was considered to be generated from the valence band–conduction band electron transition of emerging zirconia composited with polymers. As the testing temperature increased, the PAM/ZrO x composite cluster gradually formed and the sol–gel transition of the ink sample occurred, which can lead to the shift and intensity change of the absorption peak. For Ink-01, the spectrum changed little below 45 °C, and the absorbance peak intensity significantly increased when the temperature reached 80 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Large SERS enhancement factors were also measured in SERS experiments on Zn-doped ZrO 2 nanoparticles [ 83 ]. Such nanoparticles were formed by the addition of triemethylamine to the aqueous solution of zirconium nitrate and zinc nitrate.…”
Section: Sers Substrates That Do Not Contain Nanostructured Metalsmentioning
confidence: 99%
“…The highest SERS activity exhibited ZrO 2 nanoparticles with 1% Zn doping. In SERS experiments with p-mercaptobenzoic acid as a Raman reporter, the SERS enhancement factor was determined as equal to 1.94 × 10 4 [ 83 ].…”
Section: Sers Substrates That Do Not Contain Nanostructured Metalsmentioning
confidence: 99%
“…Many studies have reported that zirconium dioxide (ZrO 2 ) has excellent properties, such as high temperature, corrosion, and oxidation resistance, thermal and chemical stability, which ensures it is widely used in the production of artificial teeth, high temperature materials, electronics and bio ceramics [20][21][22]. Specifically, nanosized ZrO 2 has three types of crystal structure: monoclinic (M), tetragonal (T) and cubic Nanomaterials 2021, 11, 2162 2 of 14 (C) [23,24], in addition to being an N-type semiconductor. Moreover, nano-ZrO 2 exhibits surface and interface, quantum size, and macroscopic quantum tunneling effects [25].…”
Section: Introductionmentioning
confidence: 99%
“…The use of semiconductor materials as SERS substrates is prevalent; however, to date, only two studies describing the use of ZrO 2 as a SERS substrate have been reported. The crystalline form of nano-ZrO 2 is mainly the M phase [ 24 , 28 ] and the EF can reach 10 3 . Nano-ZrO 2 is very suitable as a SERS substrate due to its superior characteristics, and using nano-ZrO 2 expands the range of semiconductor nanomaterials as SERS substrates.…”
Section: Introductionmentioning
confidence: 99%